Determinants of Early Childhood Teachers' Subjective Well-being in Indonesian Archipelagic Regions: A Demographic and Social Factors Analysis - Sagita, Dony Darma; Simarmata, Sari Wardani; Nisa, Uliya Khoirun; Santos, Luis (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to analyze demographic and social factors that influence Subjective Wellbeing (SWB) of PAUD teachers in the archipelago. The research method uses a quantitative approach with a cross-sectional design, the research sample is 223 teachers. The sampling technique uses convenience sampling. The instrument used is the Teacher Subjective Wellbeing Questionnaire (TSWQ). The results showed that all demographic variables, namely age, gender, education level, and teaching experience, have a positive and significant relationship to SWB, with education level being the strongest predictor among demographic factors (r = 0.352**). Meanwhile, in social factors, the principal's leadership showed the highest correlation (r = 0.441**) to SWB, followed by co-worker support, community involvement, and relationships with students' parents. These findings indicate that teacher SWB is not only influenced by individual characteristics, but also by the quality of social interactions in the work environment and community. This study recommends the importance of strategies to improve teacher SWB through strengthening professional capacity and a supportive work environment.┬á┬á